Study of the decay Bs(0)-->Ds(*)Ds(*). - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2007)
We report a study of the decay Bs(0)-->Ds(*)Ds(*) using a data sample corresponding to 1.3 fb(-1) of integrated luminosity collected by the D0 experiment in 2002-2006 during run II of the Fermilab Tevatron collider. One Ds(*) meson was partially reconstructed in the decay Ds-->phi mu nu, and the other Ds(*) meson was identified using the decay Ds-->phi pi where no attempt was made to distinguish Ds and Ds(*) states. For the branching fraction Br(Bs(0)-->Ds(*)Ds(*)) we obtain a 90% C.L. range [0.002,0.080] and central value 0.039(-0.017)(+0.019)(stat)(-0.015)(+0.016)(syst). This was subsequently used to make the most precise estimate of the width difference DeltaGamma(s)CP in the Bs(0)-Bs(0) system: DeltaGamma(s)CP/Gamma(s)=0.079(-0.035)(+0.038)(stat)(-0.030)(+0.031)(syst).